Icosahedral silicon boride: a potential hybrid photovoltaic-thermoelectric for energy harvesting - Xia, Kang (2023)
Boron-rich compounds have attracted significant attention due to their promising and diverse physical properties, which include ultrahardness, resistance to oxidation and corrosion, and even superconductivity. Here, using a crystal structure search method based on first-principles calculations, we find a boron-rich silicon compound SiB12 that is stable under moderate pressure of around 20 GPa, and which we predict is recoverable to ambient pressure. This silicon boride, with space group Pnnm, is structurally related to the γ-B28 boron phase. Specifically, the SiB12 structure is formed by replacing the B2 pairs in γ-B28 with silicon atoms. Our calculations show that this Pnnm SiB12 phase exhibits good thermal stability at moderate pressures above 20 GPa and temperatures to 900 K. We suggest this structure has dynamic stability at ambient pressure and remains stable to temperatures as high as 2000 K. Impressively, this SiB12 phase possesses good light absorption and thermoelectrical properties, which are enhanced by its small and indirect band gap, doubly degenerate bands, and low lattice thermal conductivity. Our predictions should stimulate further investigations of this class of boron-rich semiconductors, especially in view of their superior photovoltaic and thermoelectric properties which may be beneficial in energy applications.